EMPIRE Registry, Czech Part: Impact of demographics, pulmonary function and HRCT on survival and clinical course in idiopathic pulmonary fibrosis. (26th September 2017) - Doubková, Martina; Švancara, Jan; Svoboda, Michal; Šterclová, Martina; Bartoš, Vladimír; Plačková, Martina; Lacina, Ladislav; Žurková, Monika; Binková, Ilona; Bittenglová, Radka; Lošťáková, Vladimíra; Merta, Zdeněk; et al.
Summary: Introduction: Prognostic factors of idiopathic pulmonary fibrosis (IPF) currently recognized include changes in vital capacity and radiologic findings. However, most of the prognostic studies in IPF are based on clinical studies with preselected IPF populations. Therefore, we decided to analyze the factors influencing IPF prognosis based on the real‐practice data from our IPF registry. Methods: Data of 514 subjects consecutively entered since 2012 into Czech EMPIRE IPF registry were analyzed. Results: Median age of our patient cohort was 67 years (50–82). Median overall survival (OS) of the cohort was 63.1 months. The clinical course of IPF according to FVC (forced vital capacity) changes was stabilized in 32.8% of patients (29.7% according to DLCO [diffuse lung capacity] changes), slowly progressive in 39.5% (45%), rapidly progressive in 23.5% (20.7%); and 1.7% patients had at least one acute exacerbation during follow‐up. Deterioration in FVC of ≥10% at month 12 and in DLCO of ≥15% at months 12, 18, and 24 influenced the OS significantly. The fast progressors defined by the DLCO decline rate had higher risk of death compared to those defined by the FVC change over time. In multivariate analysis, age ≥70 years, interstitial HRCT scores ≥3, and change in DLCO of ≥15% at month 12 were confirmed as factors negatively influencing OS. Conclusions: DLCO changes over time were shown as a better predictor of mortality compared with FVC changes in our study. In our opinion it is necessary to implement the DLCO analysis into clinical trials and routine practice.